Simulation of the production and remediation of water from acid rock drainage (ARD) - Lovera, Daniel (2001)
Technologies are currently being developed for the treatment of acid mine drains (DAM), rock drainage (ARD) and other industrial effluents, which are causing water and soil contamination. Natural acid drainage is one of the foci of environmental contamination in national watersheds and for this reason it is necessary to search for the appropriate technologies to reduce it to suitable environmental conditions. Environmentally sound technologies protect the environment, are less polluting, use all resources more sustainably, recycle a larger portion of their waste and products, and treat waste more acceptably than the technologies they have come to replace. In the present work we show the experimental study of acid rock tests in percolation columns, in which we try to reproduce what happens in the Peruvian mines, this leads us to simulate the main variables that are involved: feed flows and percolation, solution acidity over time, metallic content in the solution, bed height, mineralogical composition and the granulometry of acid rocks. We will also seek the remediation of the environmental contamination of said effluents, for this we will use neutralization processes, chemical precipitation of the metal ions present, appropriate use of flocculants; to finally have an effluent that meets the international "maximum permissible limits". Finally, a model has been designed that accurately describes the process, which implies simulating the parameters under other operating conditions according to the type of acid rock that the drainage generates.